ANALYSIS OF THE FINANCIAL FEASIBILITY OF THE LAYER DUCK (Anas sp) BREEDING BUSINESS IN SEUNEBOK BARU VILLAGE, MANYAK PAYED DISTRICT, ACEH TAMIANG - Zahra, Alvina; Basriwijaya, Kiagus M. Zain; Saragih, Faoeza Hafiz (AGRIBUSINESS JOURNAL, 2024)
This research aims to analyze the cost structure and profitability of the broiler duck farming business (Anas Sp) in Batee Puteh village, Langsa Lama sub-district, Langsa city. The method used is a survey method and direct interviews with breeders. The population in this study were breeders who cultivated broiler ducks with an ownership scale of more than 100 individuals, totaling 2 people. The method used in sampling is the Census Method, namely by taking the entire population to be used as a sample. The data collected includes primary data and secondary data. The research results show that the cost structure incurred by breeders consists of: fixed costs amounting to IDR 4.473.535,-/year with a percentage of 2,98% and variable costs as big as IDR 79,369,000/year with a percentage of 52,91%. The total income received by duck breeders in Batee Puteh Village is IDR151.200.000,-/year with total production costs of IDR83.842.535,-/year thereby generating huge profits IDR67.357.465,-/Year and IDR5.613.122,-/Month with the average profit being IDR33.678.733,-/Year and IDR2.806.561,-/Month. Based on the results of the sensitivity analysis under normal conditions and after changes in production, a 5% decrease in production, a 10% increase in feed prices and a 15% decrease in cage usage costs indicate that the duck farming business in Batee Puteh Village is still feasible to run.